South Asia in transition : conflicts and tensions - Bahadur, Kalim; Indian Centre for Regional Affairs (New Delhi : Patriot Publishers, 1986)
Papers presented at a seminar organized by the Indian Centre for Regional Affairs, 1985.
Includes bibliographies and index.
Keywords: South Asia -- Politics and government; South Asia -- Social conditions